Encyclopedia of case study research - Durepos, Gabrielle; Wiebe, Elden; Mills, Albert J. 1945- (Los Angeles, [California] London SAGE, 2010)
This resource for case study research provides a thorough overview of methods and design as guidance for students researchers and professionals who wish to incorporate case studies into a research project or programme.
Title from title screen (viewed October 19, 2023)
Keywords: Research -- Methodology -- Encyclopedias